The West Indies in Records from colonial missionaries, 1704-1950. (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2010)
This missionary work contrasted with the same Society owning slaves in the West Indies. These reports cover both sides of the Society's legacy as it moved from owning slaves to educating the emancipated. As this archive was held by the United Society for the propagation of the Gospel, the 'Letters Sent' are those sent by their head office. The 'Letters Received' are those written by missionaries in the colonies. The plantation covered in 'The Codrington collection' was a charitable gift to the USPG in 1710. It was intended to be a school for educating slaves, but became a source of income and a school for white children. It would take more than a century before black children were educated there. The 'C series' includes letters 'sent' and those 'received', with a focus on Jamaica and Barbados.
Date range: 1704-1950.
Keywords: Missions -- West Indies -- History; West Indies -- History; United Society for the propagation of the Gospel